2019
DOI: 10.3356/jrr-18-00002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation among Island and Continental Populations of Burrowing Owl (Athene cunicularia) Subspecies in North America

Abstract: Burrowing Owls (Athene cunicularia) have a large geographic range spanning both North and South America and resident populations occur on many islands in the eastern Pacific Ocean and the Caribbean Sea. Many owl populations are isolated and disjunct from other populations, but studies on genetic variation within and among populations are limited. We characterized DNA microsatellite variation in populations varying in size and geographic isolation in the Florida (A. c. floridana), the Western (A. c. hypugaea), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Microsatellite loci represent reliable molecular markers to describe genetic variability or its drastic reduction, as demonstrated by Macías-Duarte et al [59] that found different values in three different populations of Athene cunicularia, with the average number of alleles varying from 2.7 in Clarion Islands to 5.1 in Florida and 22.5 in Western North America.…”
Section: Discussionmentioning
confidence: 96%
“…Microsatellite loci represent reliable molecular markers to describe genetic variability or its drastic reduction, as demonstrated by Macías-Duarte et al [59] that found different values in three different populations of Athene cunicularia, with the average number of alleles varying from 2.7 in Clarion Islands to 5.1 in Florida and 22.5 in Western North America.…”
Section: Discussionmentioning
confidence: 96%
“…with molecular genetic analyses, although, again, the paucity of modern West Indian specimens of Burrowing Owl (few skins, 3 partial skeletons, no tissues) precludes such analyses at this point. For example,Macías-Duarte et al (2019) did not include any West Indian samples in their genetic analyses of Burrowing Owls. Nevertheless, we suspect that late Pleistocene gene flow occurred between Burrowing Owls in Florida and The Bahamas, especially given the large number of other species of birds shared between Florida and The Bahamas at that time(Steadman and Franklin 2015, 2017).…”
mentioning
confidence: 99%